On an acoustic method for the determination of the density of a liquid as a function of pressure - Joachim GMYREK (Archives of Acoustics)
On the basis of Schaaffs paper and Gruneisen's theory it has been shown that the Rao expression at constant temperature does not depend on the pressure. It results from the stability of the Rao-Schaaffs expression that it is possible to determine the density of a liquid as a function of pressure by the intermediary of quantities measured exclusively under normal pressure. The method provides a better agreement of the calculated values with experimental ones than do other methods.